SOCIEDADE INFORMACIONAL E CRIPTOMOEDAS: análise comparativa da atuação do Superior Tribunal de Justiça e do Conselho Administrativo de Defesa Econômica na efetivação do Direito Antitruste no Brasil. - FERREIRA, Carlos Anderson dos Santos (2020)
The development of new technologies within the scope of the information society has allowed for the emergence of economic activities that promote the breaking of paradigms, such as, for example, the new types of financial assets called cryptocurrencies. In spite of the short time of its existence, commercial transactions using cryptocurrencies are experiencing exponential growth in Brazil, exceeding the volume of business carried out on the Stock Exchange in the last year. The disruptive nature of technology, the speed at which commercial activities are increasing and the lack of a central authority to control operations have aroused the concern of national financial institutions, especially the main Brazilian retail banks, which have suffered the greatest impacts from market from the competition promoted by the entry of cryptocurrency brokers into the private investment market, a circumstance that motivated the unilateral closure of these brokers' bank accounts. In this scenario, the general objective of this research is to evaluate comparatively the performance of STJ and CADE for the enforcement of Antitrust Law in the country, taking as a reference the case involving the unilateral closure of cryptocurrency brokerage bank accounts. With support from the theoretical framework of Manuel Castells, the main characteristics of the information society are studied, as well as its importance for the development of cryptocurrencies and their uses for the economy. After, based on the constitutional principles of free initiative and free competition, as well as the idea of a contract as a legal guise of economic operations, a qualitative analysis of the decisions made by STJ and CADE is promoted based on the provisions provided for in Law 12.529/2011, with a special focus on the normative provision of acts that constitute an infraction of the economic order. It is concluded that the analyzed decisions do not contribute to the effectiveness of Antitrust Law in Brazil, as they no longer consider the practice of banks to promote the unilateral closure of bank accounts of brokers as abusive, increasing transaction costs by creating artificial barriers for potential competitors to enter the relevant market. This study has been carried out using the deductive approach, the monographic procedure and the bibliographic method of reserach.